Framework Administered Account for Selected Fund Activities : Government of Australia Subaccount for Selected Fund Activities. (Policy Papers; Policy Paper ;, 2013)
In March 2009, the Fund adopted the Instrument to establish a new Framework Administered Account to administer external financial resources for Selected Fund Activities (the 'SFA Instrument').1 The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of subaccounts. This paper requests Executive Board approval to establish the Government of Australia Subaccount for Selected Fund Activities (the 'Subaccount') under the terms of the SFA Instrument.